Promises of “development” to Latin America: experts, scientists and the United States technical cooperation projects (1949-1954) - Abreu Damasceno, Natália (2021)
This article discusses the roles of experts and scientists in United States’ technical cooperation projects in Latin America during the early Cold War. Amongst global changes, in which US’ international leadership was earmarked, a larger conception of national security set technical assistance as a permanent element in Washington’s foreign policy. In this context, the ideas of economists and social scientists, and the job of agronomists and technicians alike helped put forward modernization projects attuned to the process of consolidation of American regional hegemony. Aiming at observing experts and scientists’ performance levels, we have created three analitical categories which demarcate different functions performed: theorists, formulators and field technicians. Out of these, we analysed the importance of the production of ‘diagnosis’ and ‘solutions’ to Latin American ‘underdevelopment’ during the post war in the Institute of Inter-American Affairs and the State Department.